Simple One-Step Synthesis of Nipa Frond-Derived Magnetic Porous Carbon for Decolorization of Acid Yellow 23 - Linh Thi Kim Nguyen; Long Quang Nguyen; Hung Minh Nguyen; Thuan Minh Nguyen; Hung Hoa Lam; Tuyet-Mai Tran-Thuy; Dung Van Nguyen (Journal of Chemistry)
Nipa is an abundant, underutilized palm whose major part is its fronds. Nipa fronds (NF) were, therefore, valorized as a renewable carbon resource for the preparation of advanced magnetic porous carbon (MPC) via simple one-step pyrolysis with FeCl3 addition as a magnetic precursor. Properties of the obtained material were determined by X-ray diffraction (XRD), nitrogen adsorption and desorption isotherms, vibrating sample magnetometer (VSM), scanning electron microscopy (SEM) images, energy-dispersive X-ray (EDX) spectroscopy, and Fourier-transform infrared (FTIR) spectroscopy. XRD results showed that Fe3O4 along with Fe0 particles were formed in the porous carbon base. FeCl3-activation of NF yielded MPC with a high specific surface area (SBET) of 330 m2/g, a large total pore volume (Vtotal) of 0.26 cm3/g, and a strong specific saturation magnetization of 7.65 emu/g. Subsequently, MPC was explored for the removal of acid yellow 23 (AY23) using H2O2 as an oxidation agent. Before H2O2 addition, MPC (0.80 g/L) at pH 3.0 partly eliminated AY23 (initial 100 ppm) with an adsorption capacity of 14.5 mg/g. In further catalytic oxidation with 200 ppm of H2O2, MPC removed 89.1% of AY23 within 120 min. Moreover, AY23 decolorization with different MPC samples obeyed pseudo-first-order kinetics, with the greatest rate constant being 0.0186 min−1. Interestingly, the utilized MPC samples could be easily removed from the treated media using a magnet. Altogether, the findings suggest that low-cost magnetic porous carbon produced from one-step pyrolysis of FeCl3-loaded nipa frond might be applied to the treatment of acid yellow 23 in wastewater due to its relative adsorption capacity, efficient catalytic performance, and powerful magnetic separability.